The Wiley‐Blackwell Handbook of Addiction Psychopharmacology 2013
DOI: 10.1002/9781118384404.oth1
|View full text |Cite
|
Sign up to set email alerts
|

Conclusions: Consilience as the Future of Addiction Psychopharmacology

Abstract: The goal of this volume was to bring together the many diverse methodologies and technologies that are used to study addictive behavior. The assembled chapters provide a range of perspectives on addiction, from top-down approaches that frame addictive disorders across the lifespan to bottom-up approaches that focus on the micro-determinants or neurobiological substrates of addiction. The single theme that is common across them all is a focus on rigorous experimental methodology and empiricism. Recognizing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Furthermore, the dependent variable of alcohol consumption was assessed via the amount of beer consumed in a mock taste-test task, and supported by BrAC assessment. This approach has a long history of use in alcohol studies as a methodology that can examine voluntary drinking while reducing demand effects (MacKillop & Murphy, 2013; Marlatt, Demming, & Reid, 1973; Thomas et al, 2011). Our data show that AUDIT-C scores were correlated with beer drinking in the taste-test task, indicating that drinking in the laboratory was related to drinking outside the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the dependent variable of alcohol consumption was assessed via the amount of beer consumed in a mock taste-test task, and supported by BrAC assessment. This approach has a long history of use in alcohol studies as a methodology that can examine voluntary drinking while reducing demand effects (MacKillop & Murphy, 2013; Marlatt, Demming, & Reid, 1973; Thomas et al, 2011). Our data show that AUDIT-C scores were correlated with beer drinking in the taste-test task, indicating that drinking in the laboratory was related to drinking outside the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The taste rating task is a common way to assess voluntary alcohol consumption under controlled conditions, while reducing demand and observation effects (MacKillop & Murphy, 2013). During this task, participants were presented with two 12-oz mugs of light beer (710 ml), and accompanied by a form with various taste descriptors (e.g., oaky, tart).…”
Section: Methodsmentioning
confidence: 99%
“…The taste-rating task is a common way to assess voluntary alcohol consumption under controlled conditions while reducing demand and observation effects ( Mackillop and Murphy, 2013 ) and is significantly associated with measures of typical consumption ( Jones et al, 2016 ). Participants were presented with two pitchers of light beer, which were poured into two 12-oz mugs (710 ml total).…”
Section: Methodsmentioning
confidence: 99%
“…This is mitigated slightly with the development of novel assays of clinical features 112,113 but remains an issue. Similarly, the translational validity of human laboratory paradigms is also imperfect 354,355 . Moreover, although there is an extensive neuroimaging knowledge base on AUDs and the brain, most studies are cross-sectional, precluding inferences about whether the observed differences are causes and/ or consequences of AUD.…”
Section: Biobehavioural and Aetiological Researchmentioning
confidence: 99%